Social representations of elderly people care and social network maps - Maldonado Brito, Annie Mehes (2017)
This study aimed to understand the social representations of elderly people self-care, care to other elders and their social network, by relating them to care practices used by social networks. The study included a survey distributed to 102 elderly subjects who were asked about their gender and dependency level, in order to identify the elderly social network and the structural part of the social representation of elderly people care. The results shown by the configuration and network map indicate a difference between gender in the elderly social network configuration, where men and independent elderly felt less loneliness, which may reflect a slight deterioration of dependent elderly’s social network. In social practice, elderly people care is assigned to informal caregivers, family members and women. The social representation of elderly people care mainly included the pragmatic aspects of care, functionality and passivity. There is a need for educational policies related to health and aging that favor not only the elderly, but also people who are close to experience old age, especially those who have become, in social practice, elderly caregivers. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.01